Incidence of Airborne Fungi in Rajshahi Metropolitan City in Relation to Seasonal Fluctuations - Begum, Most Ferdousi; Alam, Shahidul; Alam, Md Shah (Journal of Life and Earth Science, 2011)
Using PDA, Saboraud's, Czapek's and Richard's media and settling plate technique, a total of 16, 593 fungal colonies belonging to 28 genera were identified during November 2006 and October 2007 in the atmosphere of the Rajshahi Metropolitan City. Seasonal fluctuations in the incidence of airborne fungi and their relation to some meteorological parameters were noticed. The incidence varied significantly by seasons. Maximum incidence of air borne fungi was recorded from November to January, where as the minimum was found from August to October. The most prevalent fungal genera were Aspergillus, Candida, Penicillium, Rhizopus, Fusarium, Alternaria, Curvularia and Cladosporium in respect of seasons. Aspergillus was the most dominting fungi contributed 25.6, 26.3, 24.4 and 26.3% in PDA, Sabouraud's, Czapek's and Richard's media, respectively during the twelve months of observation. The percentage contributions of the most predominant 14 genera were 83.1, 84.1, 83.9 and 885.6 collected in PDA, Sabouraud's, Czapek's and Richard's media, respectively. Rest of the 14 genera were covering about 8.3, 8.0, 7.1 and 84.2% of the total aero-fungi and sterile mycelium and unidentified fungi were contributed 7.8, 7.4, 8.4 and 8.1%, respectively. Key words: Airborne fungi; incidence; culture media; season; fluctuation. DOI: 10.3329/jles.v3i0.7444 J. Life Earth Sci., Vols. 3-4: 37-41, 2009